A Socio-Economic Analysis of Youth Disconnectedness - Friedhelm Pfeiffer; Ruben R. Seiberlich (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
Disconnectedness among youth can have several dimensions. From a socio-economic viewpoint, failure in school, unemployment and the lack of an intimate relationship are among the most important ones. In our samples from SOEP youth questionnaires, approximately 13% of young people in Germany between the ages of 17 and 19 are disconnected. The percentage of disconnected youths has been on the rise since 2001. There is evidence that an adverse family background is the most important variable for being disconnected in young adulthood. Macroeconomic factors also contribute to disconnectedness. Recessions are followed by increases in the number of disconnected youth.
Keywords: D87; I12; I21; J13; 330; Disconnected youth; unemployment; school failure; life adversity; Jugendliche; Soziale Integration; Bildungsverhalten; Familiensoziologie; Deutschland